IMPLEMENTASI KEBIJAKAN PROGRAM ZERO WASTE CITY DALAM MEWUJUDKAN SMART ENVIRONMENT DI KOTA DEPOK - Silvia Shyfa Azani; Dini Gandini Purbaningrum (Jurnal PubBis, 2023)
The Zero Waste City Program is a policy regarding waste management in Depok City from 2016 until 2024. The program aims to free all areas in Depok City from all types of waste. However, in reality, there are still problems regarding waste management that are not carried out properly so in several areas the City of Depok has not been free from waste problems. Several areas in Depok City include Pancoran Mas District, Sukmajaya District, Cimanggis District, Tapos District, and Sawangan District. The purpose of this study was to determine the Implementation of the Zero Waste City Program Policy in Creating a Smart Environment in Depok City. This research uses a descriptive method with a qualitative approach and uses the theory of policy implementation according to Van Meter and Van Horn. Data collection techniques used are observation, interviews, and documentation. The determination of informants amounted to 14 people by using a purposive sampling technique. Data processing uses triangulation techniques with sources. The conclusion this study, the results of this study indicate that the implementation process of the Zero Waste City program policy in Depok City has not been optimal. There are 4 indicators of policy implementation that experience obstacles from the other 6 indicators. In the standard indicators, policy targets experience obstacles to the achievement of the objectives to be achieved. In terms of policy resource indicators, the obstacle is the quantity of DLHK field officers who are limited in outreach. On the attitude indicator of implementers, socialization efforts that are carried out are not routinely carried out. Social, economic, and political environmental indicators have obstacles in social support that have not fully supported the Zero Waste City program in Depok City.